Peningkatan Kapasitas Pekerja Sosial Melalui Pelatihan Caregiver Lansia dan Bantuan Hidup Dasar di Panti Sosial DKI Jakarta - Dinni Agustin; M. Robby Fajar Cahya; Kwarnanto Kwarnanto; Tina Rosa; Alfian A. Durandt (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
This study aimed to evaluate the effectiveness of an Elderly Caregiver and Basic Life Support (BLS) training program in improving the capacity of social workers in institutional settings. A pre-experimental one-group pre-test and post-test design was applied involving 108 participants. The training was conducted through lectures, simulations, case discussions, and hands-on practice. Data were analyzed using Shapiro–Wilk normality test, paired-sample t-test, effect size (Cohen’s d), and 95% confidence interval. The results showed a significant increase in mean scores from 61.99 to 84.16 (p < 0.001). The effect size was very large (d = 6.55), with a 95% confidence interval ranging from 21.53 to 22.80. This program effectively improves social workers’ knowledge in elderly care and emergency preparedness in social institutions.